Re-thinking discourses of “youth” within (adult) regulation of skateboarding - Petrone, Robert (Frontiers in Sports and Active Living, 2024)
Situated within the context of increasing “adult regulatory practices” in skateboarding, this article draws attention to and interrogates the ways normative ideas of “youth,” “adolescence,” and “youth/adolescent development” often interplay with such efforts. In doing so, this article offers a critique, from a Critical Youth Studies perspective, of dominant, developmentalist notions of youth that typically cast young people as deficits in need of specific forms of intervention and surveillance. The article concludes with areas of inquiry emergent from critiques of dominant renderings of youth to be considered when engaging in processes of forming regulatory programs, policies, and practices related to skateboarding.